2020
DOI: 10.2478/rjim-2020-0024
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant protein S in COVID-19: low activity, and associated with outcome

Abstract: Introduction: COVID-19 disease was associated with both thrombo-embolic events and in-situ thrombi formation in small vessels. Antiphospholipidic antibodies were found in some studies.Aim: Assessment of protein S activity in patients with COVID-19 as a cause this prothrombotic state, and of the association of protein S activity with worse outcome.Methods: All patients admitted for COVID-19 disease in a university hospital between 15th of May and 15th of July 2020 were prospectively enrolled into this cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 29 publications
(33 reference statements)
5
29
0
Order By: Relevance
“…Factor V synergistically stimulates PROS1 activity. 57 Stoichitoiu et al ( 55 ) showed a correlation between PROS1 activity and clinical severity and lung damage. 55 All three studies showed that PROS1 activity (free Protein S) was below the normal range in COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factor V synergistically stimulates PROS1 activity. 57 Stoichitoiu et al ( 55 ) showed a correlation between PROS1 activity and clinical severity and lung damage. 55 All three studies showed that PROS1 activity (free Protein S) was below the normal range in COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“… 51 , 52 Blood clots have been reported in cases of COVID-19 and SARS; however, data for the few cases of MERS are scarce. 53 Lemke et al , 54 Zhang et al , 59 and Stoichitoiu et al ( 55 ) have postulated that depletion of Protein S may be related to the observed hypercoagulability of the blood. Lemke et al ( 54 ) and Stoichitoiu et al ( 55 ) also proposed that PROS1 deficiency may play a role in the immune hyper-reactions observed in humans with COVID-19 since PROS1 is involved in the activation of immunosuppressive TAM (Tyro3, Axl, and Mer) receptors that prevent hyperinflammation and lung injury.…”
Section: Resultsmentioning
confidence: 99%
“…A study investigating the effect of baseline protein S activity of 91 patients, with survival as the main outcome, revealed protein S activity to be reduced in 65% of the patients; death was associated with lower activity of protein S (median 42 vs. 58%, p < 0.001). 94 Another study showed a significant decrease in protein S activity of patients compared with the control group. 91 Two other studies reported protein S activity slightly below the normal range.…”
Section: Natural Anticoagulantsmentioning
confidence: 97%
“…Its influence on coagulation is palpable since protein S deficiencies are related to elevated thrombotic risk [ 83 ]. Clinical data revealed low activity of protein S in COVID-19 patients, suggesting this may contribute to coagulopathy in COVID-19 [ 84 , 85 ]. Also, backing this suggestion, SARS-CoV-2 papain-like protein cleaves a sequence within protein S, and this cut may result in impaired protein S function or secretion in the course of the viral infection [ 5 ].…”
Section: Enzyme Dysregulation Consequencesmentioning
confidence: 99%